2014
DOI: 10.1364/oe.22.018625
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the quasi-TE mode (in-plane) graphene linear absorption coefficient via integration with silicon-on-insulator racetrack cavity resonators

Abstract: Abstract:We examine the near-IR light-matter interaction for graphene integrated cavity ring resonators based on silicon-on-insulator (SOI) racetrack waveguides. Fitting of the cavity resonances from quasi-TE mode transmission spectra reveal the real part of the effective refractive index for graphene, n eff = 2.23 ± 0.02 and linear absorption coefficient, α gTE = 0.11 ± 0.01dBμm −1 . The evanescent nature of the guided mode coupling to graphene at resonance depends strongly on the height of the graphene above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The quality factor (λ/Δλ) of the MRR cavity resonance decreases from ~9000 to ~7500 after GO deposition. This relatively small change suggests that the absorption of light by the GO is not as strong as for graphene 33,36 , which is a key aspect for a functional layer for MRR based gas or vapour sensing, where a high quality factor is preferred, for a given detection resolution, in order to be able to measure relatively small shifts in the resonant wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…The quality factor (λ/Δλ) of the MRR cavity resonance decreases from ~9000 to ~7500 after GO deposition. This relatively small change suggests that the absorption of light by the GO is not as strong as for graphene 33,36 , which is a key aspect for a functional layer for MRR based gas or vapour sensing, where a high quality factor is preferred, for a given detection resolution, in order to be able to measure relatively small shifts in the resonant wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with evanescent-wave devices based on microfibers, waveguide-integrated devices offer smaller footprints. Crowe et al [32] studied light-matter interactions in graphene-based silicon-on-insulator (SOI) racetrack cavity resonators and by optimizing the thickness of the separation spacer layer between graphene and the waveguide, the maximum sensitivity can be achieved. Lim et al [33] demonstrated a humidity sensor by integrating GO on the SU-8 waveguide.…”
Section: Waveguide-integrated Graphene Photonic Devices For Sensing Amentioning
confidence: 99%
“…This may be overcome, at least in part, by using slotted, concentric- [6,7], cascaded- [8] or subwavelength-grating (SWG)-RRs [9] or by the integration of functional layers, capable of better adsorbing or chemically activating, surface-bound molecular analytes. In some cases, such approaches were also reported to provide a degree of selectivity [10][11][12].…”
Section: Introductionmentioning
confidence: 99%